2023
DOI: 10.3390/en16062685
|View full text |Cite
|
Sign up to set email alerts
|

Power Quality Disturbances Characterization Using Signal Processing and Pattern Recognition Techniques: A Comprehensive Review

Abstract: Several factors affect existing electric power systems and negatively impact power quality (PQ): the high penetration of renewable and distributed sources that are based on power converters with or without energy storage, non-linear and unbalanced loads, and the deployment of electric vehicles. In addition, the power grid needs more improvement in the performances of real-time PQ monitoring, fault diagnosis, information technology, and advanced control and communication techniques. To overcome these challenges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 218 publications
(292 reference statements)
0
7
0
Order By: Relevance
“…Different future works can be suggested for the proposed research and architecture. The main ones are as follows: The development of LDN prototypes with different communication standards, both wired and wireless; The characterization of the system even in the presence of more than one PQ events at the same time; The product engineering of the LDN; The development of the CCU, making it capable of classify the PQ events and evaluating the characteristic parameters of the recognized event [ 53 , 54 , 55 ]; The development of a methodology and of a prototype suitable for three-phase systems. The literature analyzed shows few studies on unbalanced three-phase systems, in particular in the case of renewable energy sources [ 56 ].…”
Section: Future Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Different future works can be suggested for the proposed research and architecture. The main ones are as follows: The development of LDN prototypes with different communication standards, both wired and wireless; The characterization of the system even in the presence of more than one PQ events at the same time; The product engineering of the LDN; The development of the CCU, making it capable of classify the PQ events and evaluating the characteristic parameters of the recognized event [ 53 , 54 , 55 ]; The development of a methodology and of a prototype suitable for three-phase systems. The literature analyzed shows few studies on unbalanced three-phase systems, in particular in the case of renewable energy sources [ 56 ].…”
Section: Future Workmentioning
confidence: 99%
“…The development of the CCU, making it capable of classify the PQ events and evaluating the characteristic parameters of the recognized event [ 53 , 54 , 55 ];…”
Section: Future Workmentioning
confidence: 99%
“…The above case is due to three major factors. The prominent factors are (1) the ability to learn from its errors, (2) verifying the accuracy of its predictions/outputs, and (3) making the necessary adjustments accordingly [7]. In addition to the above, it is found that, generally, DL performance increases proportionally to the training dataset's volume.…”
Section: Introductionmentioning
confidence: 98%
“…With many inherent and associated issues in power systems, particularly in smart grids and microgrid environments, PQ disturbance monitoring and detection is indispensable for secure, reliable, well-controlled, and protective system operation [1]. An advanced monitoring system with proper techniques to analyze PQ events is required to meet the consumer's requirements for a quality power supply.…”
Section: Introductionmentioning
confidence: 99%
“…One of the leading causes of poor power quality is the occurrence of anomalies within the supply signals, known as power quality disturbances (PQD). Identifying the occurrence of these phenomena in the supply systems is a critical step because poor PQ can cause equipment malfunction and damage, a decreasing AC motor speed, relay malfunction, and the downtime of computers, among others [8,9]. In addition, real-time PQD monitoring can help to take faster actions to mitigate PQ issues, and it is a way of knowing the PQD propagation along the grid [10].…”
Section: Introductionmentioning
confidence: 99%